Pengaruh Prinsip Bagi Hasil Terhadap Preferensi Masyarakat pada Perbankan Syariah Wilayah Kota Pontianak - Yudhi, Mohamad (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
This study aims to find out how the effect of the principle of profit sharing on people's preferences in Islamic banking in the city of Pontianak. Data collection techniques in this study used questionnaires / questionnaires with a population in the form of Pontianak city community who had become customers of Islamic banks.The sampling technique uses convenience sampling. The research method used is simple regression analysis using the help of IBM SPSS version 25 software.The research results obtained indicate that the principle of profit sharing has a significant effect on people's preferences in Islamic banking in the city of Pontianak. Community preference variables can be explained by the principle of profit sharing of 4.7%, while 95.3% is explained by other variables outside the research.Â Keywords: Profit Sharing Principles, Community Preferences.Daftar PustakaAndespa, R. (2017). Analisis Faktor-faktor Yang Mempengaruhi Minat Nasabah Dalam Menabung di Bank Syariah. Al Masraf: Jurnal Lembaga Keuangan dan Perbankan-Volume 2, Nomor 1.Bawono, A. (2006). Multivariate Analysis dengan SPSS. Salatiga: Salatiga Press.Ghozali. (2016). Aplikasi Analisis Multivariete dengan Program IBM SPSS 23. Semarang: Badan Penerbit Universitas Diponegoro.Ismail. (2011). Perbankan Syariah. Jakarta: Prenada Media Group.Karim, A. A. (2011). Bank Islam Analisis Fiqih dan Keuangan. Jakarta: Rajawali Pers.Kotler, P. (2000). Manajemen Pemasaran. Jakarta: Prehalindo.Lestari, A. (2016). Pengaruh Kepemimpinan Partisipatif dan Komitmen Organisasi Terhadap Efektifitas Implementasi Rencana Stratejik Pada Madrasah Aliyah di Kabupaten Sukabumi Jawa Barat. Jurnal Administrasi Pendidikan Vol. XXIII No.1.Mangkunegara, A. A. (2012). Perilaku Konsumen. Bandung: Refika Aditama.Mustafa EQ, Z. (2013). Mengurai Variabel Hingga Instrumentasi. Yogyakarta: Graha Ilmu.Narbuko, C. &. (2013). Metode Penelitian. Jakarta: Bumi Aksara.Nugroho, J. S. (2013). Perilaku Konsumen. Jakarta: Kencana Prenada Meida Group.OJK. (2018). Statistik Perbankan Syariah. Diambil kembali dari Otoritas Jasa Keuangan (OJK): http://www.ojk.go.idPriadana, M. S. (2009). Metodologi Penelitian Ekonomi & Bisnis. Yogyakarta: Graha Ilmu.Priyaatno, D. (2010). Paham Analisis Statistik Data dengan SPSS . Yogyakarta: MediaKom.Rahmawaty, A. (2014). Pengaruh Tentang Bank Syari'ah Terhadap Minat Menggunakan Produk di BNI Syari'ah Semarang. ADDIN.Sari, N. E. (2017). Penerapan Prinsip Bagi Hasil dan Pengaruhnya Terhadap Keputusan Menabung Nasabah Bank Muammalat Kantor Cabang Madiun.Sarip Muslim, S. M. (2015). Akuntansi Keuangan Syariah. Jakarta: Pustaka Setia.Sri Fadilah, N. A. (2017). Analisis Preferensi Masyarakat Akademis pada Produk-Produk di Perbankan Syariah (Studi Pada Dosen Perguruan Tinggi Islam di Bandung Raya). Kajian Akuntansi.Sugiyono. (2015). Metode Penelitian Pendidikan Pendekatan Kuantitatif, Kualitatif dan R&D. Bandung: Alfabeta.Suparno. (2009). Persepsi Mahasiswa Fakultas Ekonomi Universitas Syiah Kuala Terhadap Perbankan Syariah Sebagai Lembaga Keuangan. Jurnal Telaah dan Riset Akuntansi, 93-103.Syafi'i, M. A. (2015). Bank Syariah : dari Teori ke Praktek. Jakarta: Gema Insani Press.Umar, H. (2007). Metode Penelitian Untuk Skripsi dan Tesis Bisnis. Jakarta: PT. Raja Grafindo Persada.Vebitia. (2017). Analisis Preferensi Masyarakat Terhadap Prinsip Bagi Hasil Pada Bank Syariah di WIlayah Banda Aceh. Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi (JIMEKA), 98-107.Yakin, H. (2015). Bagaimana Kepuasan Nasabah Terhadap Pelayanan Produk Tabungan iB Tadharus pada PT. Bank Kalbar Syariah.Yopie. (2018). Jumlah Penduduk Kota Pontianak Semester II Tahun 2018 Capai 665.694 Jiwa. Diambil kembali dari DISDUKCAPIL KOTA PONTIANAK: http://www.disdukcapil.pontianakkota.go.idYossiana, A. Y. (2018). Pengaruh Produk Bagi Hasil Tabungan Mudharabah Terhadap Minat Menabung Nasabah Bank Syariah Mandiri Kantor Cabang Pembantu (KCP) UleeÂ